Особливості цвітіння і запилення витких жимолостей в умовах інтродукції - Muzyka, G.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The findings of the investigation of florescence and pollination characteristics of introduced ramble honeysuckles in the introduction conditions are cited. The characteristics of the ramble honeysuckles' pollen, the characteristics of the pollen germination depending on the composition of nutrient medium, the correlation of the pollen fertility to the flowering stage of the ramble honeysuckles are established.